Pengaruh Kesadaran Lingkungan Mahasiswa Tata Rias UNJ terhadap Minat Beli Produk Green Cosmetic - Amanda, Kerin Nadila; Armandari, Mari Okatini; Ambarwati, Neneng Siti Silfi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Environmental damage and pollution have negative effects on living creatures in it. Therefore, various efforts are made to increase people's environmental awareness. A characteristic that someone has environmental awareness is their efforts to consume environmentally friendly products. One of the products that is widely consumed today is cosmetic products. With the shift in people's consumption patterns towards environmentally friendly products, cosmetics industries are starting to use green cosmetic principles in their products. This product is in demand by the younger generation because it is good for their health and the environment. The aim of this research is to determine the influence of UNJ Cosmetology students' environmental awareness on their interest in purchasing green cosmetic products. The research method used is associative quantitative. The results obtained from this research are that UNJ Cosmetology students' environmental awareness influences their interest in buying green cosmetic products.